Progress in disease resistance and yield potential: an analysis of VEF - EP Nurseries (1979 - 1986) - Amézquita, María Cristina; Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1987)
Using the data generated by VEF (vivero equipo de frijol) and EP (ensayo preliminar de rendimiento) nurseries during 1979-86, the progress of the CIAT Bean Program during this 8-yr period of plant breeding effort is described in terms of the production of disease resistant lines and the attainment of high-yield-potential lines with disease resistance attributes. The analysis of disease reaction evaluations of VEF-EP nurseries shows an increasing trend in the production of bean lines resistant to the 5 diseases considered (rust, anthracnose, angular leaf spot, common bacterial blight, and BCMV). There are enough sources of combined disease resistance to satisfy specific regional needs. Twenty-five percent of the 1257 lines tested at EP nurseries in the 3- yr period between 1984 and 1986 are high yield potential lines. (CIAT)